OPTIMALISASI SISTEM INFORMASI AKUNTANSI TERHADAP PENCAPAIAN KARAKTERISTIK KUALITATIF LAPORAN KEUANGAN PEMERINTAH - Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2018)
Abstract: This study examines the phenomenon of West Java Provincial Government's financial statements that received unqualified opinion (WTP) from the Supreme Audit Board (Badan Pemeriksa Keuangan) prepared after qualify the qualitative characteristics aspects of a good Financial Statement. This study aims to test how much influence the availability of hardware and software availability as a major component of Accounting Information Systems which became a tool to produce government financial statements. The research method used is survey with primary data collection tool in the form of questionnaire. The relationship between research variables was analyzed by using multiple regression analysis with SPSS tool. The results showed that 1). there is a significant positive influence from the availability of Hardware and Software Availability collectively to the qualitative characteristics of the Municipal / Regency Government Financial Statements in West Java. 2). Hardware availability has a significant positive effect on Qualitative Characteristics of Government Financial Statements. 3). Software availability has a positive but insignificant effect on the qualitative characteristics of government financial statements. Keywords: Accounting Information System, Hardware Availability, SoftwarevAvailability, Qualitative Characteristics of Government Financial Statements